Suitable scale structures for urban multi-functions: an integrative approach grounded in socio-ecological system analysis - Wuyang Hong; Shuwen Yang; Renzhong Guo; Yelin Li; Lin Jiang; Xiaoming Li (Ecological Processes)
Abstract Aims Research on the appropriate scale structure and spatial layout of ecological, urban, and agricultural spaces and the effective and methodical development and protection of urban space can provide a solid foundation for the sustainable development of the complex socio-economic urban environment. Methods Based on the perspective of a coupled social-ecological system, this paper constructed an assessment model to determine the ecological protection importance and development suitability of urban space, proposed the ecological-urban-agricultural priority for densely populated urban areas, and established the appropriate functional layout of urban space using a priority matrix-based mapping method. Results Through an empirical case study of Shenzhen, this paper determined the optimal scale structure of the types of functional spaces, identified areas of functional conflict, and proposed targeted optimization strategies for functional mismatch areas. The findings show that the appropriate scale ratio of Shenzhen’s urban, ecological, and agricultural functions is 5:4:1, which is consistent with the actual structure ratio of Shenzhen’s land use trends. Conclusions The proposed method can predict the appropriate scale structure of urban space development and ecological protection based on the comprehensive multi-perspective consideration of social and economic factors to provide a scientific reference for effective decision-making on urban space optimization and sustainable development.